2019
DOI: 10.3390/microorganisms7090329
|View full text |Cite
|
Sign up to set email alerts
|

Maize Inoculation with Microbial Consortia: Contrasting Effects on Rhizosphere Activities, Nutrient Acquisition and Early Growth in Different Soils

Abstract: The benefit of plant growth-promoting microorganisms (PGPMs) as plant inoculants is influenced by a wide range of environmental factors. Therefore, microbial consortia products (MCPs) based on multiple PGPM strains with complementary functions, have been proposed as superior, particularly under challenging environmental conditions and for restoration of beneficial microbial communities in disturbed soil environments. To test this hypothesis, the performance of a commercial MCP inoculant based on 22 PGPM strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 39 publications
2
20
1
2
Order By: Relevance
“…This is in line with recent follow-experiments, which showed significant stimulatory effects on the respective enzymatic activities in the maize rhizosphere only in a soil substrate with extremely low background activities of the respective enzymes, reflecting a low microbial activity due to long-term dry storage of the respective soil for more than 20 years. By contrast, on a freshly collected field soil, as similarly used in the present study, the inoculant effects were completely superimposed by high background activities of the rhizosphere marker enzymes exceeding the recorded MCP-induced changes by two orders of magnitude (Bradáčová et al 2019b). This point to beneficial MCP effects on nutrient cycling and mineralisation preferentially expressed in heavily disturbed soil environments with limited microbial activities but not in fertile agricultural soils.…”
Section: Resultscontrasting
confidence: 49%
“…This is in line with recent follow-experiments, which showed significant stimulatory effects on the respective enzymatic activities in the maize rhizosphere only in a soil substrate with extremely low background activities of the respective enzymes, reflecting a low microbial activity due to long-term dry storage of the respective soil for more than 20 years. By contrast, on a freshly collected field soil, as similarly used in the present study, the inoculant effects were completely superimposed by high background activities of the rhizosphere marker enzymes exceeding the recorded MCP-induced changes by two orders of magnitude (Bradáčová et al 2019b). This point to beneficial MCP effects on nutrient cycling and mineralisation preferentially expressed in heavily disturbed soil environments with limited microbial activities but not in fertile agricultural soils.…”
Section: Resultscontrasting
confidence: 49%
“…+ absorption [21,22]. The range of the pH drop following NH 4 -N supply was similar [25,41] or higher [42] than that reported for ryegrass by other authors, which is likely due to the differences of pH buffering capacity between the studied soils [31,43,44]. 2.…”
Section: Bulk Soil and Rhizosphere Phsupporting
confidence: 72%
“…The lower root biomass under NH 4 -N supply ( Table 5; Table 6) is consistent with the well-reported inhibition effect of aluminum toxicity on root growth [52] and may in turn impair P uptake by plants. For instance, in the rhizosphere of NH 4 -N fed maize, Bradáčová et al [43] found that the pH decrease from 6.1 to 4.6 resulted in a 60% reduction in root growth, which in turn limited P uptake by plants. Table 4.…”
Section: Effect Of N Forms On P Uptakementioning
confidence: 99%
“…(2012) in in vitro gnotobiotic conditions and Bradácová et al. (2019) in soils with low organic matter content. On the other hand, some studies have revealed a deleterious impact of inoculation with bacterial strains on plant growth under gnotobiotic conditions due to the accumulation of bacterial toxic metabolites (Rybakova et al., 2016; Timmusk et al., 2015).…”
Section: Discussionmentioning
confidence: 94%